A statistical approach to recognizing source classes for unassociated sources in the first fermi-LAT catalog - Ackermann, Markus; Grondin, Marie-Hélène (The astrophysical journal, 2012)
The Fermi Large Area Telescope (LAT) First Source Catalog (1FGL) provided spatial, spectral, and temporal properties for a large number of γ -ray sources using a uniform analysis method. After correlating with the mostcomplete catalogs of source types known to emit γ rays, 630 of these sources are “unassociated” (i.e., have no obvious counterparts at other wavelengths). Here, we employ two statistical analyses of the primary γ -ray characteristics for these unassociated sources in an effort to correlate their γ -ray properties with the active galactic nucleus (AGN) and pulsar populations in 1FGL. Based on the correlation results, we classify 221 AGN-like and 134 pulsar-like sources in the 1FGL unassociated sources. The results of these source “classifications” appear to match the expected source distributions, especially at high Galactic latitudes. While useful for planning future multiwavelength follow-up observations, these analyses use limited inputs, and their predictions should not be considered equivalent to “probable source classes” for these sources. We discuss multiwavelength results and catalog cross-correlations to date, and provide new source associations for 229 Fermi-LAT sources that had no association listed in the 1FGL catalog. By validating the source classifications against these new associations, we find that the new association matches the predicted source class in ∼80% of the sources.
Gesehen am 06.11.2018